The Effect of Adding Papaya Leaf Flour (Carica Papaya L.) on The Nutritional Content of Pellet - Salsabella, Marshanda Valentina; Sariri, Ahimsa Kandi (Jurnal Biologi Tropis, 2025)
Feed has a crucial role in enhancing livestock growth and productivity, both in terms of nutritional composition and physical characteristics. One approach to improve feed quality is the utilization of natural ingredients rich in nutrients, such as papaya leaf flour (Carica papaya L.). This research aimed to evaluate the impact of adding papaya leaf flour on the nutritional composition of feed pellets. The study was carried out over five months at the Microbiology Laboratory, Faculty of Agriculture, Bangun Nusantara University, Sukoharjo, and at the Animal Science Laboratory, Diponegoro University. A Completely Randomized Design (CRD) was employed with three treatments and four replications: F0 (100 g of pellet without papaya leaf flour), F1 (100 g of pellet + 3% papaya leaf flour), and F2 (100 g of pellet + 6% papaya leaf flour). Observed parameters included dry matter, crude fiber, and crude protein. Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) when significant differences occurred. The results demonstrated that adding papaya leaf flour significantly affected dry matter and crude fiber contents but did not significantly influence crude protein levels.